2000
DOI: 10.3354/meps204093
|View full text |Cite
|
Sign up to set email alerts
|

Local variability but landscape stability in coral reef communites following repeated hurricane impacts

Abstract: Coral reef community structure has remained remarkably stable over a 10 yr period within a small protected marine area despite repeated hurricane impacts. Local community dynamics have been highly variable, however. Sites that were destroyed by disease in the 1970s are showing little or no recovery, while sites less than a kilometre away that were devastated by Hurricane Hugo in 1989 are recovering well. Strong coral recruitment has occurred in shallow, exposed areas that showed the greatest hurricane impacts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 36 publications
4
76
0
1
Order By: Relevance
“…Physical disturbances can have lasting effects on coral communities (Hughes and Connell 1999;Bythell et al 2000), and impact studies following Hurricane Andrew revealed that disturbance was very patchy (Tilmant et al 1994;Blair et al 1994). Further, historical changes to coral communities can affect competitive interactions among benthic organisms many years after the disturbance event (Hughes 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Physical disturbances can have lasting effects on coral communities (Hughes and Connell 1999;Bythell et al 2000), and impact studies following Hurricane Andrew revealed that disturbance was very patchy (Tilmant et al 1994;Blair et al 1994). Further, historical changes to coral communities can affect competitive interactions among benthic organisms many years after the disturbance event (Hughes 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of hurricanes in the Florida Keys over the last 50 years can be considered minimally important at the regional scale, but probably important at the scale of individual reefs (see Bythell, Hillis-Starr, and Rogers 2000). Significantly, the recent period of Acropora decline in Florida (the late 1970s to early 1980s) was coincident with an extended period of no major hurricanes.…”
Section: Hurricanesmentioning
confidence: 99%
“…Geister (1980) explained that the almost exclusive occurrence of M. annularis in the Key Largo Limestone indicates protected conditions or a growth depth below normal wave base. It has been shown, however, that corals of the M. annularis species complex are extremely robust and resistant to the effects of storms, including hurricanes (Stoddart 1963;Woodley et al 1981;Graus, Macintyre, and Herchenroder 1984;Woodley 1992;Bythell, Hillis-Starr, and Rogers 2000;Jackson and Johnson 2000), and that their distribution and zonation are due to a combination of factors including, but not limited to, competitive interactions with other corals-notably the Acropora species Rylaarsdam 1983;Tunnicliffe 1983;Huston 1985;Aronson and Precht 2001b). In fact, large, centuries-old colonies of the M. annularis species complex appear to be the most resistant corals to catastrophic hurricanes in the Caribbean (Stoddart 1963;Woodley 1992;Aronson and Precht 2001b).…”
Section: The Pleistocene Reef Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Reef zones may respond dissimilarly to the variety of stressors. Although disease appears to have been the cause of much of the mortality of Acropora palmata (typically less than 5 m deep) and A. cervicornis in the late 1970s and 1980s [117,210], and of the die-off of the important sea urchin grazer Diadema antillarum [211], at least some of the shallow reef zones with these coral species have not been carpeted with macroscopic algae that can radically reduce recruitment [212,213]. Perhaps there has not been a shi to macroalgal dominance in some of these locations because grazing is more intense in shallow water or heavy wave action periodically removes the macroalgae from the reef.…”
Section: Biodiversity and Resiliencementioning
confidence: 99%